Evaluasi Usability Protoype Aplikasi Jemput Sampah Online Menggunakan Metode System Usability Scale - Anak Agung Bagus Yoga Udiana,; I Ketut Gede Suhartana,; I Putu Satwika, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
In Indonesia, waste management is a big problem for the environment since not enough people are involved and there aren't any integrated systems. To solve this problem, a prototype mobile app called JEMPOL (Jemput Sampah Online Langsung) was made. It offers an online waste collecting service and instructional functions. The goal of this study was to evaluate the application of JEMPOL prototype. This stufy used the Design Thinking process to make sure that the application was user-centered.  The System Usability Scale (SUS) approach was used to evaluate the application with 20 people who are the intended users. The average SUS score was 70.38, which puts it in the "Acceptable" range on the Acceptability Range of SUS, gives it a "C" grade, and is rated "OK" to "Good" on the Adjective Rating scale. These results show that users generally like and can use the JEMPOL prototype, although the score differences suggest that some parts of the interface may be better. The application has a lot of promise for being used more to get more people involved in digital waste management.
Keywords: System Usability Scale; Design Thinking; Prototype Aplication; Waste Management